Role of Hyperbaric Oxygen Therapy in Traumatic Brain Injury: A Systematic Review of Randomized Controlled Trials - Raj, Sumit; Thanneeru, Suresh K; Mondithokha, Sukumar; Chouksey, Pradeep; Janjua, Tariq; Singh, Bharti; Moscote-Salazar, Luis Rafael; Yunus, Md; Agrawal, Amit (Indian Journal of Neurotrauma, 2024)
Traumatic brain injury (TBI) is a significant public health concern. Standard care involves conservative management and pharmacological and surgical interventions. Hyperbaric oxygen therapy (HBOT) has emerged as a potential treatment for TBI, with varied findings in the literature. Our systematic review aims to comprehensively assess the efficacy and safety of HBOT in TBI management, addressing existing knowledge gaps and providing insights for clinical practice and future research.A systematic literature search was performed in PubMed, SCOPUS, Central Cochrane Registry of Controlled Trials (The Cochrane Library), and ScienceDirect databases for the role of HBOT in TBI. We included studies involving randomized controlled trials (RCTs). Quasi-randomized controlled studies, prospective, retrospective observational studies, case series, case reports, letters, editorials, comments, animal studies, and studies from non-English literature were excluded.After identifying 306 articles, we narrowed it to 8 for qualitative synthesis. The studies were categorized into subgroups: those on patients with an acute history of cerebral injury and those with a history of mild TBI. The combined RCTs involved 651 patients (326 in the first subgroup, 325 in the second). Despite a uniform HBOT session duration of 60 minutes, variations in compression, decompression phases, and pressure used (1.5ATA to 2.5ATA) hindered meta-analysis comparability. Outcome measures differed, complicating comparisons. Overall, HBOT appears beneficial in the first group and less so in the second. Complications are primarily pulmonary, which include dyspnea, cyanosis, hyperoxic pneumonia, and increased fraction of inspired oxygen requirement.Our study encountered challenges in reaching definitive conclusions due to outcome variability among the included studies. Despite mixed results, HBOT shows potential benefits for acute TBI patients. Conversely, our findings suggest the limited efficacy of HBOT for chronic traumatic brain injury patients. Further research is crucial, particularly exploring diverse HBOT treatment protocols to establish optimal pressure levels and the required number of sessions for effective outcomes
Keywords: hyperbaric oxygen therapy; traumatic brain injury; posttraumatic stress disorder